Workshop Pola Hidup Bersih dan Sehat Untuk Siswa MI Simpang Kabupaten Sukabumi - Anggun Fergina; Aulia Kusuma Wardani; Sehan Zaki Nurmilad; Ardelia Ramadhani; Ahmad Dinar; Alya Nurhalisah (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2025)
This community service activity aimed to increase awareness and understanding of clean and healthy living behavior among elementary school students. The workshop, held on August 7, 2025, at MI Simpang, involved interactive learning sessions and practical demonstrations, including proper handwashing techniques. Students actively participated in the activities and showed great enthusiasm. As a result, the workshop successfully improved students’ knowledge and personal hygiene awareness. This initiative is expected to contribute to the creation of a cleaner and healthier school environment.